Development of an Index to Measure the Exposure Level of UN Peacekeeper-Perpetrated Sexual Exploitation/Abuse in Women/Girls in the Democratic Republic of Congo. (October 2022) - Gray, Samantha; Stuart, Heather; Lee, Sabine; Bartels, Susan A
Sexual exploitation and abuse (SEA) of women and girls by United Nations (UN) peacekeepers is an international concern. However, the typical binary measurement of SEA (indicating that it occurred, or it did not) disregards varying exposure levels and the complex circumstances surrounding the interaction. To address this gap, we constructed an index to quantify the degree to which local women and girls were exposed to UN-peacekeeper perpetrated SEA. Using survey data ( n  = 2867) from the Democratic Republic of Congo (DRC), eight indicators were identified using a combination of qualitative (thematic analysis of narrative data) and quantitative variables. With further development, this index may offer a more comprehensive and nuanced perspective of peacekeeper-perpetrated SEA that can better inform SEA prevention and intervention efforts.